Reseña del proyecto “Nariz de payaso. Una estrategia para la transformación social y la convivencia” - Ocaña Muriel, Silvia (Avances en Supervisión Educativa, 2026)
The “Clown Nose” Project was launched in 2017 as a proactive response by CEIP Reyes Católicos in Santa Fe to growing social concern about school bullying. Seven years later, it has been consolidated in its 2.0 version, evolving into an interdisciplinary network of strategies that extends beyond the classroom to raise awareness of and combat six areas of discrimination: school bullying, cyberbullying, eating disorders, loneliness among the elderly, sexism in sports, and the exclusion of people with functional diversity. With 0% of bullying cases recorded since its implementation, the project has become an international benchmark for educational innovation.
Keywords: project, campaign, interdisciplinary community network, school bullying, inclusion, emotional intelligence, educational innovation